Factorial Validity and Reliability of a Food Behavior Checklist for Japanese Pregnant and Postpartum Women - Fujita, Megumi; Yamaguchi, Sanae; Banna, Jinan; Suzuki, Asuka (Journal of Maternal and Child Health, 2023)
Background: Dietary education programs for pregnant and postpartum Japanese women are conducted during health check-ups and in childbirth education classes, but there is no tool to evaluate their food behavior. Therefore, this study examined the factorial validity, test–retest reliability, and internal consistency of the food behavior checklist (FBC) for pregnant and postpartum Japanese women. Subjects and Method: This was a longitudinal study. We screened 4,000 women aged 18–45 years who were either pregnant or nursing an infant aged <1 years and enrolled in Freeasy, a platform with 4.5 million panels. Data were collected from 97 pregnant women and 203 postpartum women through an online survey. They completed the 21-item FBC on a web survey twice at an interval of 3 weeks. After performing principal component analyses, internal consistency was calculated using Cronbach’s α. The intraclass correlation coefficient (ICC) and kappa (κ) coefficient were calculated to assess the test–retest reliability. Results: There were 21 items loaded on six factors (fruit and vegetable quantity, vegetable variety, balanced fish and meat intake, sweetened beverages, eating habits, and food consciousness). Cronbach’s α for the total scale was 0.77. ICC for the test–retest reliability of individual items ranged from 0.35 to 0.62, and ICC for the total scale was 0.62. The κ coefficient values ranged from 0.26 to 0.52, indicating fair-to-moderate strength of agreement between the test and retest. Conclusion: The FBC demonstrated factorial validity, test–retest reliability, and internal consistency, indicating its potential application in evaluating the effects of the dietary education programs on pregnant and postpartum women, which include taking a staple meal, folic acid, and avoiding raw food consumption. This compact tool can be conveniently used by midwives and provide practical guidance during maternal health check-ups. Keywords: pregnant, postpartum, dietary, checklist, reproducibility. Correspondence: Megumi Fujita. Yamagata University, 2-2-2 Iida Nishi Yamagata, 990-9585, Japan. Email: f.megumi@med.id.yamagata-u.ac.jp Mobile: + 81 23-628-5443.